First principles calculations of electronic structures and optical properties of Al- and Ca-doped β-Si3N4. (1st April 2013) - Lu, X F; Qiu, D; Chen, M; Fan, L; Wang, C; Wang, H J; Qiao, G J
Abstract : The crystal structures, formation energies, electronic structures and optical properties of Al- and Ca-doped β -Si3 N4 were studied using first principles calculations based on density functional theory within the generalised gradient approximation. Results show that the band gaps E g of Al- and Ca-doped β -Si3 N4 decrease distinctly in comparison to that of β -Si3 N4 . The band structures of Ca-doped supercell behave like semiconductors. The binding energy E b and formation energy E f of β -Si3 N4 doped with Al are lower than those of Ca-doped β -Si3 N4, indicating that the former has a more stable crystal structure than the latter. The static dielectric constant (0) increases significantly to ∼35 after Al doping and almost does not change after Ca doping. The strong absorption band located at 5·11-20·81 eV becomes much sharper and shows a red shift after Al and Ca doping. The offset of the Al-doped system is larger than that of the Ca-doped system. The absorption coefficient can be remarkably modulated by Al and Ca doping, indicating the potential applications of Al- and Ca-doped β -Si3 N4 in optical system.